Development and Standardization of Dental Plant-Based Preparation in The Republic of Uzbekistan - Aziza A. Djuraeva1, Viloyat N. Abdullabekova2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Nowadays herbal medicines are widely used in official medical practice in Uzbekistan. At the same time,the most common among both imported and domestic plant-based preparations are liquid dosage forms.The modern stage of application of these medicines is based on the rational use not only of the accumulatedexperience, but also on the achievements of scientific medicine in the study of the composition and featuresof biological activity of medicinal plants and isolated from them active compounds. Studies have shown thatthese drugs contain unique in composition combinations of biologically active substances, providing a widerange of therapeutic and preventive action. To solve the problem developed the composition and obtainedon its basis a liquid extract for the treatment of diseases of the oral cavity of the mixture of plants such aschamomile drug, sage drug, St. John’s wort, calendula drug in the ratio of raw materials - extraction fluid1:1, established the most optimal extraction fluid - 70% ethyl alcohol and obtained alcohol extraction.The resulting liquid extract was conditionally called “Parodonfit” and analyzed according to therequirements of regulatory documentation. Each of the plants has its own quality standard. Qualitativeand quantitative analyses of biologically active substances of liquid extract “Parodonfit” with the use ofphysical and chemical method, such as thin layer chromatography, chromatography spectrophotometry, gasliquidchromatography was carried out. Biologically active substances in the liquid extract - flavonoidsand tannins - were determined during the research. The sum of flavonoids was determined by TLC, wherecompounds of routine, quercetin, cinarozid were isolated. Qualitative analysis of tannins and determinationof heavy metals were conducted by pharmacopoeia method. Quantitative determination of active substancesof cinarozid by chromatospectrophotometry was carried out. The tannins in recalculation for tannin - 3,2% and in recalculation for proanthocyanides - 6,38 % were found out by chemical reactions according tothe GD (governing documents). Quality indicators for liquid extract “Parodonfit” have been developedaccording to the requirements of the normative document: physical and chemical indicators, ethyl alcoholconcentration, heavy metals, microbiological purity. The received results have shown perspective andexpediency of development of highly effective multicomponent medical products on the basis of medicinalvegetative raw materials.